Matriculation 2005. Photo 013 - Loeb, Brian (Tufts Archival Research Center, 2008)
Matriculation 2005. Orientation volunteers blowing up balloons in Dowling Hall 701 and distribute them around campus before the new class arrives. Includes Orientation Coordinators Anita Sinha, LA '06, and Kate Drizos, LA '06.